Pengembangan Media Pembelajaran Pendidikan Kesehatan Melalui Kartu Sehat (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
This study aims to produce the model of health education through health cards for class VIIISMP Islam Al Madina Semarang. This research is a development which refers to the modelof development of Brog and Gall, with steps as follows: 1) conduct a needs analysis of theresults of field observation, interviews and review of the literature, 2) develop initial product,3) expert evaluation of physical education and expert teaching physical education, as well asthe trial I (n = 12), 4) revision of the initial product, 5) test II (N = 29), 6) a revision of thefinal product, 7) the final results of the health card. The results of this study is the validationdata of the experts of healthy education and two experts learning in the initial product beforethe test I, the trials I, and trial II, the average results of the assessment are expert healthyeducation 79% (good) and learning experts 86,5% (good), the tests I obtained the results ofthe questionnaire the average percentage of selection of an appropriate response 81% (good).As for the second test of the questionnaire results the average percentage corresponding answerchoice 92.75% (excellent). Based on the results, it can be concluded that the health card mediais completely unfit for learning physical education in improving students’ knowledge of healtheducation for the students of class VIII SMP Islam Al Madina Semarang.